Haste intramedular bloqueada confeccionada com polímero biocompatível para imobilização de fraturas em fêmures de bovinos jovens: análise in vivo - Odael Spadeto Junior (2009)
This study is part of a proposal for development of a low-cost and easy-to-use polymeric interlocking nail, initially designed to use in newborns and young cattle. The objectives of the present study are to evaluate in vivo the polymeric interlocking nail system for fixation of femoral fractures in calves, and to compare these results with those obtained in a previous ex vivo mechanical testing and computational simulation using finite element method, in order to validate the computational simulation system for future projects. Five calves were used. Under general anesthesia, all animals had the left femur fractured and then fixed using the polymeric interlocking nail system. In the postoperative period, animals were clinically assessed using radiological and ultrasound techniques during 60 days. Of the five polyacetal rods (nails) used in the first surgeries, four broken at 3, 6 and 11 days after surgery. In two animals that had the same material reimplanted, new fractures occurred 3 and 9 days after the second surgery. Four animals were implanted with polyamide rod, two after the first broken polyacetal rod and the other two after the second broken polyacetal rod. From these, one calf showed fracture of the polyamide rod 14 days after the third surgery and the other animal showed fracture 12 days after the second surgery. Blood cytological and biochemical tests did not show evidence of lack of biocompatibility by the used materials. The in vivo results confirmed the findings of the computational simulation system, which predicted that polyacetal and polyamide would not have sufficient strength to sustain the fixation of the fracture until bone healing. The findings of this experiment validate the computational model developed by the Biomechanics Research Group of UFMG